Heuristic analysis of the presence of information policies in open access legal databases in Brazil - Ribeiro, Patrick Fernandes Rezende; Araújo, Paula Carina de (Advanced Notes in Information Science, 2024)
This study was conducted as part of the project entitled “Management of Scientific Information in the Context of Open Science,” which was funded by the National Council for Scientific and Technological Development (CNPq). The objective of this study is to analyze the information policies of open access databases dedicated to the field of law in Brazil. The study’s specific objectives are threefold: (a) to define the concept of information policy and its impact on the creation of a national open access database dedicated to the field of law, (b) to map the main databases in the field of law based on the recognition of their maintaining institutions, and (c) to describe the elements that make up the existing information policies in the databases analyzed in this research. The research employs an exploratory approach and a heuristic analysis based on an analytical tool. The results demonstrate the existence of these policies in the databases under examination, although not always explicitly. This, therefore, highlights the importance of this presence in order to consolidate information management in legal databases and to fulfill one of the principles of open science, namely transparency.